Bentuk Penerapan Eko-Efisiensi pada Rantai Nilai di Klaster Batik Laweyan, Kota Surakarta - Nurrizki Dwianto Widodo (Jurnal Wilayah dan Lingkungan, 2013)
Eco-efficiency is suitable to be applied on batik production cluster, because it can synergize economic and environmental aspects. Application of eco-efficiency will lead to competitiveness, environmental sustainability, and quality of life better. Batik Laweyan cluster is a cluster that not only has great potential in regional economic development but also potentially pollute the environment. Application of eco-efficiency in an industrial cluster can be seen from the value chain that occurs. Eco-efficiency also cannot be applied without the aid of relevant stakeholders and cluster activities such as collective efficiency.